181: Screening for Post-Traumatic Stress Disorder After Injury in the Pediatric Emergency Department – A Systematic Review. Issue 6 (1st June 2014) - Odenbach, J; Newton, A; Gokiert, R; Falconer, C; Courchesne, C; Campbell, S; Curtis, S
Abstract: BACKGROUND: Pediatric injury is highly prevalent and has significant impact both physically and emotionally. The vast majority of pediatric injuries are treated in emergency departments (EDs), where treatment of physical injuries is the main focus. In addition to physical trauma, children often experience significant psychological trauma, which often goes unrecognized. The development of posttraumatic stress disorder (PTSD) is common, sometimes even after seemingly mild trauma. The consequences of failing to recognize childhood PTSD are stark and extend into adulthood. Currently, screening guidelines to identify children at risk for developing for these stress disorders do not exist in the pediatric emergency setting. OBJECTIVES: The goal of this systematic review is to summarize evidence on psychometric properties, diagnostic accuracy, and clinical utility of screening tools that identify or predict PTSD in children and adolescents with acute injury. DESIGN/METHODS: Computerized databases including MEDLINE, EMBASE, CINAHL, ISI Web of Science and Psychological Abstracts/PsycINFO were searched and included MeSH headings (posttraumatic stress or acute stress), (pediatric or children) and diagnosis. After duplicate removal, titles and abstracts were screened by two independent reviewers for eligibility and taken for full text review. Quality of included studies was assessed using the QUADAS tool for diagnostic accuracy. RESULTS: A total of 10, 415 articles were screened by title/abstract by two independent reviewer reviewers and 228 potentially relevant articles were retrieved in full text. Interrater reliability (kappa) score of 0.833 was calculated for article screening. Screening tool characteristics; including type of instrument, number of items and administration time as well as quantitative diagnostic data (specificity, sensitivity, positive and negative likelihood/odds ratios, as appropriate) were compiled for 89 screening tools. Of these tools, we identified one immediate use risk assessment tool and 88 symptom assessment tools including three clinician-administered screening tools, 56 self-report screening tools, seven parent-report screening tools and 22 (semi-) structured diagnostic interviews. CONCLUSIONS: Numerous PTSD screening tools exist and span a wide variety of clinical pediatric settings. Although most tools are overly complex and lengthy to be suitable for ED use, a small number of simple/abbreviated tools exist and further research is warranted to determine their efficacy in the ED setting of pediatric injury.